Blood flow speed of the gastric conduit assessed by indocyanine green fluorescence: New predictive evaluation of anastomotic leakage after esophagectomy. Issue 30 (July 2016) - Koyanagi, Kazuo; Ozawa, Soji; Oguma, Junya; Kazuno, Akihito; Yamazaki, Yasushi; Ninomiya, Yamato; Ochiai, Hiroki; Tachimori, Yuji
Abstract : Abstract: Anastomotic leakage is considered as an independent risk factor for postoperative mortality after esophagectomy, and an insufficient blood flow in the reconstructed conduit may be a risk factor of anastomotic leakage. We investigated the clinical significance of blood flow visualization by indocyanine green (ICG) fluorescence in the gastric conduit as a means of predicting the leakage of esophagogastric anastomosis after esophagectomy. Forty patients who underwent an esophagectomy with gastric conduit reconstruction were prospectively investigated. ICG fluorescence imaging of the gastric conduit was detected by a near-infrared camera system during esophagectomy and correlated with clinical parameters or surgical outcomes. In 25 patients, the flow speed of ICG fluorescence in the gastric conduit wall was simultaneous with that of the greater curvature vessels (simultaneous group), whereas in 15 patients this was slower than that of the greater curvature vessels (delayed group). The reduced speed of ICG fluorescence stream in the gastric conduit wall was associated with intraoperative blood loss ( P = 0.008). Although anastomotic leakage was not found in the simultaneous group, it occurred in 7 patients of the delayed group ( P < 0.001). A flow speed of ICG fluorescence in the gastric conduit wall of 1.76 cm/s or less was determined by a receiver operating characteristic (ROC) curve, identified as a significant independent predictor of anastomotic leakage after esophagectomy ( P = 0.004). This preliminary study demonstrates that intraoperative evaluation of blood flow speed by ICG fluorescence in the gastric conduit wall is a useful means to predict the risk of anastomotic leakage after esophagectomy.